2021
DOI: 10.1177/15248380211043825
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Childhood Maltreatment on Self-Compassion: A Systematic Review and Meta-Analysis

Abstract: Background: This systematic review aims to estimate the extent to which childhood maltreatment influences self-compassion in later life. Method: Four English databases (Web of Science, PsycINFO, PubMed, and PsycARTICLES) and three Chinese databases (China National Knowledge Infrastructure, Wanfang, and Weipu) were systematically searched. We extracted data related to the associations between child maltreatment and self-compassion and pooled them using random effect models. Findings: A total of 20 eligible stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…As to the relationship between CM and mindfulness, it has been reported that people who suffered from CM were observed lower level of mindfulness [12,14]. Moreover, CM was negatively correlated with self-compassion [16], and it has been found that mindfulness-based interventions can improve self-compassion [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As to the relationship between CM and mindfulness, it has been reported that people who suffered from CM were observed lower level of mindfulness [12,14]. Moreover, CM was negatively correlated with self-compassion [16], and it has been found that mindfulness-based interventions can improve self-compassion [17].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has been accumulating regarding to the beneficial role of dispositional mindfulness in various mental health problems for children and adolescents, a lower level of dispositional mindfulness had been associated with higher risk of anxiety, depression, and dissociation [12,13]. Some published studies suggested that dispositional mindfulness may play a mediating role in the association between CM and SI: a cross-sectional study of 177 young adults revealed that victims of CM reported lower level of dispositional mindfulness [14], moreover, mindfulnessbased interventions were found effective in reducing SI among Chinese children and adolescents, probably through the mechanisms of reducing pain and stress, strengthening emotion regulation ability, and improving self-compassion [15][16][17]. Nevertheless, no existing study has ever discussed this possible mediation via mindfulness in the association between CM and SI.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the classic fail-safe N , Egger’s tests, and the trim-and-fill method were employed. The fail-safe N calculated the number of potential unpublished studies with nonsignificant findings required to reduce the pooled effect size in the meta-analysis to below the level of significance (Zhang et al, 2021). In accordance with the established principles, selective publication bias exists when the fail-safe N is less than 5 times the number of published studies plus 10 (Rosenthal, 1979).…”
Section: Methodsmentioning
confidence: 99%
“…A meta-analysis indicated that emotional neglect was negatively correlated to self-compassion ( 107 ). This finding is essential since self-compassion is considered an essential protective factor after a child has experienced neglect.…”
Section: Other Psychological Factorsmentioning
confidence: 99%